Formulation Strategy to Prevent Sticking in Calcium Carbonate–Cholecalciferol Chewable Tablets: The Role of Citric Acid - Hestiary Ratih; Oke Setiawan Gosepa; Fikri Alatas; Titta Hartyana Sutarna (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2026)
The sticking phenomenon is a critical issue in the production of calcium carbonate–cholecalciferol (vitamin D3) chewable tablets, primarily driven by the hygroscopicity and reactivity of citric acid, which is used as a flavor-masking agent. This study aims to evaluate and determine the optimal method for mitigating sticking by modifying citric acid excipients using two approaches: granulation with mannitol (F1: 0.5%, F2: 1%) and coating with HPMC (F3: 0.5%, F4: 1%). The evaluation was conducted on the properties of the granule mass and quantitatively measured the percentage of sticking in industrial-scale modifications for 24 hours. The results showed that the control formula (F0), without modification, had the lowest sticking percentage (10.88%) and the highest moisture content (3.36%), as indicated by a